Macrophytes in neotropical aquaculture farms: Positive and negative effects - Sipaúba-Tavares, Lúcia Helena [UNESP]; Dias, Samuel Generoso [UNESP]; Travaini-Lima, Fernanda [UNESP]; Scardoeli-Truzzi, Bruno [UNESP]; Boareto, Cecília Anatriello [UNESP] (My University, 2014)
Aquatic plants play a significant role in maintaining water quality, due to their ability of absorbing nutrients. The aim of this chapter is to show the value of macrophyte use as a tool for biological water treatment of aquaculture farms and also as a culture medium for microalgae. In southeastern Brazil, aquaculture farming is mainly carried out in flowthrough systems, in which large earthen fishponds are commonly arranged in line, each pond receiving the effluent from the previous one, without any prior treatment. The continuous water flow through the fishponds strongly depends on seasonal rains. The current system for production of aquatic organisms could benefit greatly from the development of low cost strategies to mitigate its impacts in the environment. Maintenance of good water quality is of primary importance to maintain an ideal culture ecosystem, with adequate feed for optimal fish yield potential, and preservation of a eutrophic situation. Fish production may cause serious environmental issues, especially when there is little concern over excessive plant growth, which can influence the functioning and structure of ecological processes in the fishponds. The use of macrophytes as bio-filter and /or wetland or as microalgae culture medium in aquaculture farms can serve as a tool for maintenance of good environmental conditions and improve the cultivation of microalgae. These microalgae can in turn be used as a nutritional source for the fish larvae, pigment in aquaculture and also as a supplementary additive in the food industry. This alternative medium should allow efficient production of microalgae, at a low cost for the laboratory. The understanding of local characteristics and development of proper feeding techniques, aimed at the integration and optimization of fish production, are important factors in obtaining and maintaining water quality appropriate for microalgae culture.